L’intervention ergonomique comme acte pédagogique - Bernard Dugué; Johann Petit; François Daniellou (Perspectives Interdisciplinaires sur le Travail et la Santé)
Ergonomics is a field of research that has, for about twenty years, produced knowledge useful for the development of intervention models and, consequently, useful for the training of ergonomists. From a model describing the possible pedagogical exchange registers, and emphasizing the possible links between the instructor, the learners and the types of knowledge, we attempt to show the interest in drawing from concepts of education sciences in order to understand and structure ergonomic intervention processes. The cases of 3 different interventions are presented. The results that we obtain allow us, first, to acknowledge that there is an educational dimension in ergonomic intervention, but also, to investigate possibilities of structuring the intervention, considering the educational objectives that we could set for ourselves as ergonomists.